Few negative effects of psychotherapy in a psychiatric day hospital: a follow-up survey to a multiprofessional treatment with acceptance and commitment therapy - Richter, Christoph; Rutschmann, Ronja; Romanczuk-Seiferth, Nina (Frontiers in Psychiatry, 2024)
While there are many studies on psychotherapy and its efficacyin terms of desired outcomesthere is comparatively little evidence on the possible negative effects of psychotherapy. The aim of this study was to investigate the possible negative effects of a multi-professional psychiatric day hospital treatment for patients with mental health disorders based on Acceptance and Commitment Therapy (ACT), including possible confounding factors. Fifty-one patients with a range of psychiatric diagnoses were assessed three months after an ACT-based psychiatric day hospital treatment. Questionnaires were used to measure negative effects of psychotherapy (INEP), subjective quality of life (WHOQOL-BREF), and symptomatology (BDI-II and SCL-90-R). Correlational analyses and group comparisons were performed to determine the relationship between the sum of reported negative effects on the one hand and symptomology, quality of life, and sociodemographic variables (gender, age, diagnosis, education) on the other hand. At least one negative effect out of a list of 18 possible effects was reported by 45% of participants, and 10% reported more than two. The number of negative effects reported correlates positively with symptomology and negatively with quality of life. The sum of reported negative effects does not correlate with age or gender and does not vary by education level and primary diagnosis. In the light of previous findings, patients included in this study showed lower rates of negative effects, both overall and at item level. Practical implications of these findings are discussed.